Warning Signs in Predicting Severe Pediatric Dengue Infection - Juliansen, Andry; Heriyanto, Rivaldo S.; Budiputri, Charista L.; Meliani, Fellisa; Muljono, Michelle P.; Chandra, Shally; Octavius, Gilbert S. (Journal of Pediatric Infectious Diseases, 2022)
Objective The uncertainty of dengue's progression from infection to its severe form represents a major health care challenge, especially in children. Clinical identification of impending clinical manifestations of severe dengue (SD), along with proper and immediate management, is crucial. Thus, this study assesses the ability of warning signs to predict SD infection in pediatric patients.Methods This cross-sectional study utilized purposive sampling using medical records from January 2015 to December 2020. Children aged 0 to 18 years diagnosed with dengue fever and SD according to the World Health Organization's 2009 criteria were included.Discussion Multivariate analysis revealed that abdominal pain (odds ratio [OR]: 16.34; 95% confidence interval [CI]: 3.78–70.64; p < 0.001), fluid accumulation (OR: 10.51, 95% CI: 1.17–94.3; p = 0.036), mucosal bleeding (OR: 4.77; 95% CI: 1.27–17.91; p = 0.021), lethargy (OR: 94.37; 95% CI: 4.92–180.79; p = 0.003), hepatomegaly (OR: 17.57; 95% CI: 2.14–144.13; p = 0.008), and increased hematocrit concurrent with a rapid decrease in platelets (OR: 6.89; 95% CI: 1.79–26.51, p = 0.005) were associated with SD infection, with a high quality of discrimination (area under the curve [AUC] = 0.96) and a high quality of fit (p = 0.73). Receiver operating characteristic analysis demonstrated that 1.5 warning signs was the optimal cut-off for predicting SD infection, with a sensitivity of 90.9 and a specificity of 89.8%.Conclusion All six warning signs were significantly associated with SD infection. The optimal cut-off for predicting SD was 1.5 warning signs.
Keywords: dengue infection; severe dengue; warning signs; pediatrics